Demographic and clinical profile of amblyopia in paediatric age group at a tertiary care centre in northern India - Raina, Ananta; Verma, Neharika; Sharma, Ashok K. (International Journal of Research in Medical Sciences, 2025)
Background: Amblyopia, also referred to as "lazy eye," is one of the most common leading causes of monocular visual impairments among children around the world. This study was aimed to study the demographic profile, type and treatment outcome of amblyopia in children visiting a tertiary care centre in Northern India. Methods: A retrospective observational study was conducted on 250 children between the ages of 3-18 years, diagnosed with amblyopia between 2020-2024 in GMC, Jammu. A patient register was developed, comprising patient’s name, age, gender, type of amblyopia and treatment outcome. The data were analysed using descriptive statistics and chi-square tests. Results: Most cases (76%) were diagnosed in children aged 3-10 years, with a male predominance (64.8%). The most common type was refractive amblyopia (48%) followed by strabismic (32%) and deprivation amblyopia (20%). Astigmatism was the most common refractive error (58.3%). Outcomes of treatment were reported, improved in 72% of cases, non-improved in 20%, and non-applicable in 8% of patients. Conclusions: Amblyopia is best addressed when detected early enough. Amblyopia burden can be significantly reduced by integrating school-based vision screening programs and addressing socio-cultural barriers. More population-based studies are needed to explore its prevalence and accompanying determinants in different contexts.